Legal Review of Divorce Cases in The Religious Court of Serang City, Banten 2025 based on Law No. 1 of 1974 Concerning Marriage - Akbar Nugraha; Dini Handayani; Hamdan Arief Hanif (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the factors that cause an increase in divorce filings by wives in the Serang Religious Court in 2025 and to examine legal protection for wives based on law No. 16 of 2019, an amandment to Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The background of this study stems from the high number of divorces filins in the last five years, which indicates domestic disharmony and changes in women’s legal awareness. The urgency of this study lies in the need to evaluate the implementation of the rights and obligations of husbands and wives and the guarantee of legal protection for wives amid increasing social dynamics. This study uses a normative juridical method combined with an empirical approach through observation and interviews with court officials and parties involved in cases at the Serang Religious Court. The results of the study show that constant disputes and arguments as well as economic problems are the dominant factors causing divorce. In addition, the study found that although legal regulations guarantee the rights of wives, implementation inthe field has not been fully effective, especially regarding the fulfillment of iddah maintenance, madhiyah maintenance, mut’ah, and the division of joint property. This study recommends strengthening access to legal aid, increasing awareness about women’s rights, and optimizing the enforcement of court decisions so that legal protection for wives can be realized in a more fair and comprehensive manner